The new true crime: how the rise of serialized storytelling is transforming innocence - Rickard, Diana C. (Alternative criminology, 2023)
"The New True Crime: How the Rise of Serialized Storytelling Is Transforming Innocence looks at how criminal justice and popular culture intersect in true crime documentaries about wrongful conviction, and what they tell us about how truth and innocence are constructed across media"--